Analysis of Financial Literacy, Financial Inclusion and Mental Accounting on Investment Decisions of The Millenial Generation in Surabaya - Febriana, Ade Tia; Armansyah, Rohmad Fuad (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
There are several factors that influence investment decision making, one of which is the psychology of the millennial generation in Surabaya in making investment decisions. The basis for making investment decisions consists of rate of return, risk and time period. Investment decisions are steps taken by individuals to place their funds in the hope of obtaining a rate of return in the future. This cannot be separated from the influence of financial literacy, financial inclusion and accounting mentality. This research aims to analyze the influence of financial literacy, financial inclusion and mental accounting on investment decisions of the millennial generation in Surabaya. This research method uses quantitative methods. The instrument used was a questionnaire. The data used is data from 152 millennial generation respondents in Surabaya and the data was analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The research results show that financial literacy, financial inclusion and mental accounting have a significant positive effect on the investment decisions of the millennial generation in Surabaya. The contribution of this research in the future can provide an overview of investment products for the millennial generation in Surabaya in making investment decisions related to the level of financial literacy, financial inclusion and mental accounting in the post-pandemic era.